Asparagine, colorectal cancer, and the role of sex, genes, microbes, and diet: A narrative review - Shen, Xinyi; Jain, Abhishek; Aladelokun, Oladimeji; Yan, Hong; Gilbride, Austin; Ferrucci, Leah M.; Lu, Lingeng; Khan, Sajid A.; Johnson, Caroline H. (Frontiers in Molecular Biosciences, 2022)
Asparagine (Asn) and enzymes that catalyze the metabolism of Asn have been linked to the regulation and propagation of colorectal cancer (CRC). Increased Asn and asparagine synthetase (ASNS) expression, both contribute to CRC progression and metastasis. In contradistinction, L-asparaginase (ASNase) which breaks down Asn, exhibits an anti-tumor effect. Metabolic pathways linked to intracellular ASNS expression and Asn synthesis are regulated by KRAS, PI3K/AKT/mTORC1, TP53, and SOX12. However, Asn abundance can be altered by factors extrinsic to the cancer cell such as diet, the microbiome, and therapeutic use of ASNase. Recent studies have shown that sex-related factors can also influence the regulation of Asn, and high Asn production results in poorer prognosis for female CRC patients but not males. In this narrative review, we critically review studies that have examined endogenous and exogenous modulators of Asn bioavailability and summarize the key metabolic networks that regulate Asn. We also provide new hypotheses regarding sex-related influences on Asn, including the involvement of the sex-steroid hormone estrogen and estrogen receptors. Further, we hypothesize that sex-specific factors that influence Asn metabolism can influence clinical outcomes in CRC patients.